Exploring COD and BOD removal from industrial wastewater using a moving bed biofilm reactor (MBBR) - Nabieh Farhami; Maryam Derakhshandeh; Hamid Kazemi Hakki (Desalination and Water Treatment)
Today, massive amounts of different effluents produced by various industries have led to severe environmental pollution, and their treatment is essential. So far, little research has been performed on the removal of biochemical oxygen demand (BOD) and chemical oxygen demand (COD) from petrochemical wastewater using a moving bed biofilm reactor (MBBR) and this is the novelty aspect of this research. In this study, the real petrochemical wastewater was treated by a biological process in an MBBR. The influence of operational variables including bioremediation time, the role of suspended microorganisms, stripping by aeration, surface adsorption, the percentage of reactant filling, initial COD, and the effect of shock and salinity on the COD removal performance were investigated. The optimal conditions occurred during 72 hr of treatment, the initial COD of 2500 mg/l and the reactant filling of 50 %. In this condition, about 78.5 % of COD, 65 % of the BOD, and 50 % of total organic carbon (TOC) were reduced. In the selected optimal conditions, the biodegradability factor of the effluent( BOD5COD ratio) before and after biological treatment was 0.4 and 0.7, respectively, which indicates the effective biodegradability of the intermediates resulting from the treatment process. According to the experimental outcomes, it was confirmed that the MBBR system is a highly suitable option for the treatment of industrial wastewater.